A Mucosal and Cutaneous Chemokine Ligand for the Lymphocyte Chemoattractant Receptor GPR15 - Ocón, Borja; Pan, Junliang; Dinh, Theresa Thu; Chen, Wenjing; Ballet, Romain; Bscheider, Michael; Habtezion, Aida; Tu, Hua; Zabel, Brian A.; Butcher, Eugene C. (Frontiers in Immunology, 2017)
Chemoattractants control lymphocyte recruitment from the blood, contributing to the systemic organization of the immune system. The G protein-linked receptor GPR15 mediates lymphocyte homing to the large intestines and skin. Here we show that the 9 kDa CC-motif containing cationic polypeptide AP57/colon-derived SUSD2 binding factor (CSBF), encoded by C10orf99 in the human and 2610528A11Rik in the mouse, functions as a chemokine ligand for GPR15 (GPR15L). GPR15L binds GPR15 and attracts GPR15-expressing T cells including lymphocytes in colon draining lymph nodes and Vγ3+ thymic precursors of dermal epithelial T cells. Patterns of GPR15L expression by epithelial cells in adult mice and humans suggest a homeostatic role for the chemokine in lymphocyte localization to the large intestines, as well as a role in homing to the epidermis during wound healing or inflammation. GPR15L is also significantly expressed in squamous mucosa of the oral cavity and esophagus with still poorly defined regulation. Identification of the chemotactic activity of GPR15 adds to its reported anti-bacterial and tumor cell growth regulatory functions, and suggests the potential of targeting GPR15L-GPR15 interactions for modulation of mucosal and cutaneous inflammation.